Testing for assortative mating based on migratory phenotypes in the Common Tern (Sterna hirundo) - Simon Piro; Angela Schmitz Ornés (Avian Research)
Tracking and mating data of Common Terns (Sterna hirundo) breeding in a single colony in north-eastern Germany were used to test for assortative mating in regards to migratory phenotypes. These birds use the eastern and western African migration routes and three different wintering areas along the African coast. However, no assortative mating was found for either migratory route or wintering area, as birds using both flyways and all three wintering areas paired randomly, which might be explained by a lack of difference in the arrival date at the colony between the groups. These results might indicate a low degree of genetic fixation of migratory route and wintering area in the Common Tern, which might hint that migratory direction and wintering sites could be passed to young terns via social learning, either by joining the parents or migratory flocks of conspecifics. If migratory phenotypes are passed on by a parent, it seems more likely that it is passed from father to young, as female Common Terns tend to leave the colony earlier and males provide the majority of post-fledging care.